2014
DOI: 10.2298/bah1401079y
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivariate logistic regression model to assess factors of importance influencing prevalence of abortion and stillbirth in Nigerian goat breeds

Abstract: The aim of the study was to investigate the application of binary logistic regression to assess the potential factors associated with the prevalence of abortion and stillbirth in indigenous goat breeds in Nasarawa State, north central Nigeria. 5,268 kidding records of does from a total of 105 traditional goat herders from the year 2010-2011 were utilized in the study. The goats which were of West African Dwarf (WAD), Red Sokoto (RS), Sahel (SH) and WAD x RS crossbred (WR) genetic groups origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…Compared to the international figures, a higher abortion percentage of 43.7% for does and 35.6% for ewes was reported from Egypt (32). In contrary, a lower abortion rate has been reported from Jordan, 10.6% in does and 2.0% in ewes (33); from Nigerian, 10.8% in does (34) and from Mexico, 3.5% in does (35). Similarly, the higher abortion percentage in lowland flocks than in highland flocks is in agreement with the report of Gebremedhin et al (22) and Fentie (31) in Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…Compared to the international figures, a higher abortion percentage of 43.7% for does and 35.6% for ewes was reported from Egypt (32). In contrary, a lower abortion rate has been reported from Jordan, 10.6% in does and 2.0% in ewes (33); from Nigerian, 10.8% in does (34) and from Mexico, 3.5% in does (35). Similarly, the higher abortion percentage in lowland flocks than in highland flocks is in agreement with the report of Gebremedhin et al (22) and Fentie (31) in Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…50 This finding is in line with previous studies 20,22 in which the reported breed significantly affected the occurrence of abortion in cattle. Similar to this result, others 51,52 also detected the significant effect of breed on the incidence of abortion in cattle in Nigeria and India, respectively. However, different from this result, some studies 40,42,53 reported that a breed of cattle was not significantly associated with the occurrence of abortion.…”
Section: Discussionsupporting
confidence: 83%
“…58,59 This result is in agreement with several reports from other countries. 17,48,51,55 However, reports in Korea, Iran, and Chile differ from this finding, 52,56,60,61 reporting the season of calving did not affect the incidence of abortion. This difference may be due to the variation in environmental conditions, breed of cattle, and management system.…”
Section: Discussionmentioning
confidence: 55%
“…However, other investigations have reported that milk production and cow parity were not associated with abortion (Moore et al, 2005). Parity status and breed were significant factors affecting the incidence of abortion (Yakubu et al, 2015). However, Haileselassie et al (2011) reported that parity status had no significant effect on the incidence of abortion.…”
Section: Risk Factors Of Abortionmentioning
confidence: 91%